Self assembled hydrophobic nanoclusters of poly(methylmethcrylate) embedded into polyvinyl alcohol based hydrophilic matrix: preparation and water sorption study - Shukla, Sandeep Kumar; Shaikh, A. Wasif; Gunari, Nikhil; Bajpai, A. K.; Kulkarni, R. A. (Journal of Applied Polymer Science, 2009)
Hydrophilic matrices containing nanosized Clusters of hydrophilic moieties have demonstrated potential applications in biomedical field. A novel hydrogel containing nanosized domains (20-35 nm) of hydrophobic moieties of poly(methyl methacrylate) (PMMA) was prepared by grafting crosslinked p ly(acrylic acid-co-methyl-methacrylate) chains onto polyvinyl alcohol (PVA) backbone using an efficient redox system. The graft copolymerization process was investigated to observe the influence of gel components on the kinetic parameters of grafting such as rate of grafting (R(g)), grafting yield (G(y)) and grafting efficiency (G(e)). The prepared graft nanohydrogel was evaluated for its water sorption potential under varying chemical composition of the gel and changing pH, temperature, and ionic strength of the swelling bath. The swelling process was also examined mechanistically and diffusion constants (D) of water molecules through the swellable nanohydrogel were also evaluated. (c) 2008 Wiley Periodicals, Inc. J ppl Polym Sci 111: 1300-1310, 2009
Keywords: graft copolymers; hydrophilic polymers; Nanocomposites; swelling